Furysong - Munda, Rosaria (New York : G. P. Putnam's Sons, 2022)
Annie and Lee are fighting for their lives--and for each other--as invading dragonfire threatens to burn their home to the ground.
Sequel to: Flamefall.
Conclusion of the Aurelian trilogy.
Keywords: Dragons -- Fiction; Fantasy fiction